Song and dance man - Ackerman, Karen, 1951-; Gammell, Stephen (New York : Scholastic Inc. by arr. with Knopf, 1988)
Grandpa demonstrates for his visiting grandchildren some of the songs, dances, and jokes he performed when he was a vaudeville entertainer.
Children's Catalog (Wilson)
Caldecott Medal/Honor
ALA Notable Books
3.8
K-3
Keywords: Entertainers -- Fiction; Grandfathers -- Fiction; Entertainers -- Fiction; Grandfathers -- Fiction; Caldecott Medal books